ESPECIALLY BIBLIONYMS BASED ON FAMOUS NOUNS (TAMADDUN NURI JURNALI, 2024)
In this article, the lexical-semantic features of biblionyms represented by proper nouns are determined. Linguistic aspects of biblionyms are highlighted based on the research of semantic features of biblionyms of historical and modern works of art.